Influence of silver nanoparticle solution on the mechanical properties of resin cements and intrarradicular dentin - Umeda Suzuki, Thais Yumi; Gallego, Juno [UNESP]; Assuncao, Wirley Goncalves [UNESP]; Fraga Briso, Andre Luiz [UNESP]; Santos, Paulo Henrique dos [UNESP] (Public Library Science, 2019)
This study evaluated the influence of silver nanoparticle on mechanical properties of the components of underlying dentin and resin cement in different regions of intraradicular dentin. Ninety extracted single-rooted human teeth were used in this study. After endodontic preparation, the teeth were divided into five groups, according to the irrigating agents: distilled water, 5.25% sodium hypochlorite, 25% polyacrylic acid, 2% chlorhexidine and 23 ppm silver nanoparticles dispersion. Then, the groups were divided in 3 subgroups (n = 6) according to the technique adopted for adhesive cementation: SUA group: Scotchbond Universal Adhesive + RelyX ARC; U200 group: RelyX U200; and MCE group: MaxCem Elite. The mechanical properties of hardness and elastic modulus were measured in resin cement and underlying dentin in ultra-micro hardness tester in different thirds of radicular dentin surface. Data were subjected to ANOVA and Fisher's test (p = 0.05). In the underlying dentin, in general, there was no statistically significant difference in different thirds of intraradicular dentin according to the different solutions used. In the resin cements, higher hardness values were found, in general, for the cervical third. When silver nanoparticle solution was used, higher mechanical properties were generally obtained for resin cement for the SBU and U200 groups, with little or no changes in mechanical properties for the dentin. Silver nanoparticle application is a viable option for irrigation the intraradicular dentin previously through the cementation process of glass fiber posts. The mechanical properties are influenced by irrigant solutions used and the depth intraradical analyzed area.